Nine Observations on Korean Child Care Support and Their Policy Implications - Heesuk Yun (Korea Development Institute (KDI), 2014)
Korea's public support system for Early Childhood Education and Care (ECEC) is in urgent need of reforms that will harmonize the objectives of social policy while improving service quality through linkages to financial assistance and information disclosure. - A shift primarily attributed to politicians, support for ECEC in Korea has risen by 2.6 times in the past four years. - Korea is the only country in the OECD where the child care facility usage rate exceeds the employment rate for mothers of infants. - As a result of its failure to consider the meaning of "free child care," Korea has developed a peculiar form of support in which the same benefits are provided to all households, regardless of the actual demand or income level - Child care support is provided unilaterally to all facilities, without any ties to quality. - Institutions may reduce service quality to turn a profit after paying high premiums for occupancy. But due to information infrastructure deficiencies, users have difficulties in accessing this information. - Disparities in user costs can amount to as much as KRW 1.5 million, with large differences in teacher education levels, but it is difficult to compare them before making a choice. - Permit restriction, which bar market access when the number of facilities exceeds the number of children in a given region, have the effect of promoting permit/certification transactions and lowering instructor compensation. - Korea should strengthen child care support infrastructure, providing the necessary child care information so that parents can spend time with their children. - Fiscal support should be tied to evaluation results, with reduced child care hours and extra availability for low-income/dual-earner households to reflect actual parent demand.
Keywords: 330